2018
DOI: 10.1038/s41598-018-20515-w
|View full text |Cite
|
Sign up to set email alerts
|

Exploring coral microbiome assemblages in the South China Sea

Abstract: Coral reefs are significant ecosystems. The ecological success of coral reefs relies on not only coral-algal symbiosis but also coral-microbial partnership. However, microbiome assemblages in the South China Sea corals remain largely unexplored. Here, we compared the microbiome assemblages of reef-building corals Galaxea (G. fascicularis) and Montipora (M. venosa, M. peltiformis, M. monasteriata) collected from five different locations in the South China Sea using massively-parallel sequencing of 16S rRNA gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 82 publications
(103 reference statements)
1
21
2
Order By: Relevance
“…The present study revealed that the coral microbiome assemblage composition was significantly different from bacterial community composition in seawater, suggesting the specific control of the coral microbiome by hosts. This was in agreement with most of the studies published to date [10,13,25]. In a thermal regime where coral species have similar environmental conditions, we observed that the top OTUs were shared by all or several coral species, suggesting rare host specificity among individual coral species.…”
Section: Effects Of Hosts and Thermal Regimes On Coral Microbiome Asssupporting
confidence: 92%
See 1 more Smart Citation
“…The present study revealed that the coral microbiome assemblage composition was significantly different from bacterial community composition in seawater, suggesting the specific control of the coral microbiome by hosts. This was in agreement with most of the studies published to date [10,13,25]. In a thermal regime where coral species have similar environmental conditions, we observed that the top OTUs were shared by all or several coral species, suggesting rare host specificity among individual coral species.…”
Section: Effects Of Hosts and Thermal Regimes On Coral Microbiome Asssupporting
confidence: 92%
“…Total genomic DNA of coral and seawater samples were extracted using a PowerSoil DNA Isolation Kit (MoBio Laboratories, Carlsbad, CA, USA) according to the manufacturer's protocol. Because V3-V4 has been the preferred region for next-generation studies and has been widely used for analysis biodiversity of marine bacteria and marine symbiotic bacteria [24,25], we selected V3 and V4 hypervariable regions for coral microbiome analysis. The V3 and V4 hypervariable regions of bacterial 16S rRNA genes were amplified with the primers 341F (5 -CCTAYGGGRBGCASCAG-3 ) and 806R (5 -GGACTACNNGGGTATCTAAT-3 ).…”
Section: Dna Extraction Amplification Pyrosequencing and Data Procementioning
confidence: 99%
“…Previous studies have also highlighted significant responses in the holobiont physiology, supporting seasonal variations (Chen et al, 2005;Ulstrup et al, 2008;Carballo-Bolaños et al, 2019). Bacterial community composition has been also described to follow a certain seasonal pattern in several coral species (Li et al, 2014;Sharp et al, 2017;Cai et al, 2018). Changes in symbiont cell density, pigment composition, and photosynthetic capacity following annual periods have also been reported (Fitt et al, 2000;Warner et al, 2002;Ulstrup et al, 2008).…”
Section: Coral Dna Methylation Displays Seasonal Trends In Response Tmentioning
confidence: 66%
“…Moraxellaceae bacteria appear in the microbiomes of many of the same coral species as Pseudomonadaceae 37 , 41 43 , 52 . Like Pseudomonads, some members of the Moraxellaceae family can break down oil 17 , 53 , and may use that ability to recycle carbon for corals.…”
Section: Discussionmentioning
confidence: 99%